1976
DOI: 10.1210/jcem-42-6-1014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin on the Basal and Stimulated Gonadotropin Levels in Normal Men and Postmenopausal Women

Abstract: The effect of melatonin on LH and FSH secretion in basal conditions and after stimulation with synthetic LHRH was studied in 3 volunteer normal men and 3 women two to five years after menopause. During the first three days of study, blood samples were obtained at 8 AM. On the second day, an iv injection of 50 mug LHRH was performed; on the third day, 2 ml of 0.9% saline were injected. In both cases, blood samples were obtained 30 and 60 minutes after the injection. On the fourth day, the subjects began melaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

1977
1977
1991
1991

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 5 publications
3
11
0
Order By: Relevance
“…In only one other study in human beings has the effect of melatonin on luteinizing hormone been examined. Small quantities of melatonin, 10 mg, given im did not depress serum LH in post-menopausal women or normal men (26). Our data are consistent with the many studies on other animal species in which pharmacologic doses of melatonin depressed the concentration of LH in the blood.…”
Section: Discussionsupporting
confidence: 90%
“…In only one other study in human beings has the effect of melatonin on luteinizing hormone been examined. Small quantities of melatonin, 10 mg, given im did not depress serum LH in post-menopausal women or normal men (26). Our data are consistent with the many studies on other animal species in which pharmacologic doses of melatonin depressed the concentration of LH in the blood.…”
Section: Discussionsupporting
confidence: 90%
“…Basal levels of LH and FSH and responses to GnRH (ALH and AFSH) were not different in melato nin-treated versus control animals. This is compatible with what has been previously observed in men and post-meno pausal women treated with intramuscular melatonin [3]. However, since our experiments were performed in the morning hours and since it has been demonstrated that in hamsters melatonin affects gonadotropin release only when administered in the afternoon hours [16], one cannot ex clude an afternoon effect of melatonin on LH and FSH in nonhuman primates.…”
Section: Discussionsupporting
confidence: 92%
“…This belief is based mainly on observations in seasonal breeding animals and their res ponse to prolonged aMT administration [9,20,24] as well as on preliminary results in man [17]. More recent studies, however, clearly revealed no alteration of serum LH and FSH concentration during acute aMT administration to hu mans [7,31]. We also failed to find any changes in mean serum gonadotropins or testosterone levels by evaluating the serum concentrations of these hormones several hours before and after aMT administration.…”
Section: Discussionmentioning
confidence: 73%
“…24], To assess the influence of aMT upon a variety of physio logical parameters in man, particularly its impact on the en docrine system, aMT has been administered in various amounts and for various time periods to more than 150 human subjects [27], On the basis of these preliminary ob servations [17,23], there is a widespread view that aMT ad ministration results in a fall in serum gonadotropin and an increase in GH [19], Recent data, however, do not confirm these earlier reports [7,15,30,31].…”
mentioning
confidence: 99%